Pretransplant Comorbidities Maintain Their Impact on Allogeneic Stem Cell Transplantation Outcome 5 Years Posttransplant: A Retrospective Study in a Single German Institution. (5th March 2014) - Chemnitz, Jens M.; Chakupurakal, Geothy; Bäßler, Maya; Holtick, Udo; Theurich, Sebastian; Shimabukuro-Vornhagen, Alexander; Leitzke, Silke; Von Bergwelt-Baildon, Michael S.; Scheid, Christof
Abstract : The introduction of reduced-intensity conditioning regimens has allowed elderly patients with preexisting comorbidities access to the potentially curative allogeneic stem cell transplantation. Patient's comorbidities at the time of treatment consideration play a significant role in transplant outcome in terms of both overall survival (OS) and nonrelapse mortality (NRM). The hematopoietic stem cell transplantation comorbidity index (HCT-CI) quantifies these patient specific risks and has established itself as a major tool in the pretransplant assessment of patients. Many single center and multicenter studies have assessed the HCT-CI score and reported conflicting outcomes. The present study aimed to evaluate the HCT-CI in a single large European transplant centre. 245 patients were retrospectively analyzed and the predictive value of the score was assessed with respect to OS and NRM. We confirm that the HCT-CI predicts outcome for both OS and NRM. Moreover, we identified age of the patient as an independent prognostic parameter for OS. Incorporation of age in the HCT-CI would improve its ability to prognosticate and allow the transplant physician to assess the patient specific risks appropriately at the time of counseling for transplant.